2016
DOI: 10.3389/fncir.2016.00101
|View full text |Cite
|
Sign up to set email alerts
|

Local Field Potentials: Myths and Misunderstandings

Abstract: The intracerebral local field potential (LFP) is a measure of brain activity that reflects the highly dynamic flow of information across neural networks. This is a composite signal that receives contributions from multiple neural sources, yet interpreting its nature and significance may be hindered by several confounding factors and technical limitations. By and large, the main factor defining the amplitude of LFPs is the geometry of the current sources, over and above the degree of synchronization or the prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
244
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 253 publications
(263 citation statements)
references
References 89 publications
3
244
0
Order By: Relevance
“…A common issue in LFP analysis is to infer whether the detected oscillations represent local activity (presumably synaptic) or else passive/return currents due to volume conduction from current dipoles located elsewhere [1,46,47]. Although RR has low amplitude in the parietal cortex, our results support the notion that it does directly and specifically impact the local network, which in turn is likely to contribute to RR appearance at the LFP level.…”
Section: Discussionsupporting
confidence: 69%
“…A common issue in LFP analysis is to infer whether the detected oscillations represent local activity (presumably synaptic) or else passive/return currents due to volume conduction from current dipoles located elsewhere [1,46,47]. Although RR has low amplitude in the parietal cortex, our results support the notion that it does directly and specifically impact the local network, which in turn is likely to contribute to RR appearance at the LFP level.…”
Section: Discussionsupporting
confidence: 69%
“…We found that fixation and saccadic effects occurred in different frequency ranges. Recent work has cautioned against the a priori labelling and filtering of LFP data, while highlighting the lack of coherence in frequency selections (Einevoll, Kayser, Logothetis, & Panzeri, ; Herreras, ). Indeed, a broad range of frequencies have been arbitrarily identified as “classical” theta, anywhere between 3 and 12 Hz (Colgin, ; Ekstrom & Watrous, ; Jacobs, ; Killian, Jutras, & Buffalo, ; Skaggs et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have challenged the "local" extent of LFPs (Canolty et al, 2010;Herreras, 2016;Kajikawa & Schroeder, 2011), raising the question of whether the measured correlations with saccade parameters could reflect eye muscle artifacts or signals coming from neighboring structures, such as the thalamus. While the gamma band effect we measured here is likely due to myogenic contamination (Katz et al, 2018;Kovach et al, 2011), we have several reasons to believe that this is not the case for the low-frequency effects.…”
Section: Myogenic Contaminationmentioning
confidence: 99%
“…Throughout this research, clear evidence has emerged showing that local spiking probability is coupled to phases of the oscillatory local field (Li et al, 1952) , resulting in theories about how these oscillations may function to aid communication among brain networks (Fries, 2005;Peterson and Voytek, 2018;Roux and Uhlhaas, 2014;Voytek and Knight, 2015) . Though we have a good understanding of how current sources summate and manifest as field potential fluctuations (forward model), interpretations of these oscillations is challenging because many different biological processes can yield the same field potential fluctuation (inverse model) Herreras, 2016;Herreras et al, 2015;Pesaran et al, 2018) .…”
Section: Introductionmentioning
confidence: 99%
“…There is a general consensus that the prominent contributor to the low frequency component of the field potential (<100 Hz) is synaptic activity (Einevoll et al, 2007(Einevoll et al, , 2013Haider et al, 2016;Mazzoni et al, 2015;Mitzdorf, 1985) , but interpretation remains complicated because the resultant field potential is significantly influenced by anatomical geometry, connectivity, tissue electrical properties, and nonsynaptic ionic currents Herreras, 2016;Lindén et al, 2010Lindén et al, , 2011Ness et al, 2016;Reimann et al, 2013) . Though relatively simple models can capture certain relationships between the field potential and neuronal activity (Gao et al, 2017;Mazzoni et al, 2015;Miller et al, 2009) , the details of the relationship between the two are mostly unknown.…”
Section: Introductionmentioning
confidence: 99%